PENGEMBANGAN MEDIA DELIMA (DENAH LINGKUNGAN RUMAH) PADA SUBTEMA BERMAIN DI LINGKUNGAN RUMAH UNTUK SEKOLAH DASAR - Fajar Setiawan (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2019)
The purpose of this study is to develop Delima (Home Plan) media on the Playing Subtema in the home environment for grade II elementary school. This type of research is research and development (Research and Development). The selection of this type of research is due to the authors developing a learning media product, namely Media Pomegranate (Plan of Home Environment) which is valid, practical, and effective. The results of the study showed that Pomegranate media developed were said to be valid because they obtained an average score of 4.8 and were in the good category. Likewise, the RPP, LK, and THB that were developed to support the use of Delima media were also said to be valid, because they obtained average scores in a row of 4.5, 4.1, and 4.3, and all were in the good category. The results of the implementation of the implementation of learning, student activities, and THB are said to be practical because they obtain an average score of 4.7 and 4.8 respectively and are in the good category. While THB students are said to be effective, because they have reached the established indicators.